2017
DOI: 10.1038/s41593-017-0025-9
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of postsynaptic proteins in regions of the human neocortex

Abstract: The postsynaptic proteome of excitatory synapses comprises ~1,000 highly conserved proteins that control the behavioral repertoire, and mutations disrupting their function cause >130 brain diseases. Here, we document the composition of postsynaptic proteomes in human neocortical regions and integrate it with genetic, functional and structural magnetic resonance imaging, positron emission tomography imaging, and behavioral data. Neocortical regions show signatures of expression of individual proteins, protein c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
78
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(87 citation statements)
references
References 62 publications
4
78
0
Order By: Relevance
“…Synapses are also highly complex at the molecular level, with >1,000 genes encoding postsynaptic proteins in excitatory synapses (Bayés et al., 2011, Bayés et al., 2012, Bayés et al., 2017, Collins et al., 2006, Distler et al., 2014, Emes et al., 2008, Husi et al., 2000, Peng et al., 2004, Roy et al., 2018, Trinidad et al., 2008, Uezu et al., 2016, Yoshimura et al., 2004). The differential expression of these proteins raises the possibility that there is high synapse diversity within the brain (Grant, 2007, Emes et al., 2008, O’Rourke et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Synapses are also highly complex at the molecular level, with >1,000 genes encoding postsynaptic proteins in excitatory synapses (Bayés et al., 2011, Bayés et al., 2012, Bayés et al., 2017, Collins et al., 2006, Distler et al., 2014, Emes et al., 2008, Husi et al., 2000, Peng et al., 2004, Roy et al., 2018, Trinidad et al., 2008, Uezu et al., 2016, Yoshimura et al., 2004). The differential expression of these proteins raises the possibility that there is high synapse diversity within the brain (Grant, 2007, Emes et al., 2008, O’Rourke et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, proteomic studies have revealed remarkable synapse complexity and diversity. In these studies, biochemically purified protein complexes from the postsynaptic density were analysed and found to contain over 1,000 different protein components (Bayes et al, 2012(Bayes et al, , 2017(Bayes et al, , 2011Collins et al, 2006;Distler et al, 2014;Emes et al, 2008;Grant, 2007;Peng et al, 2004;Roy et al, 2018;Trinidad, Specht, Thalhammer, Schoepfer, & Burlingame, 2006;Trinidad et al, 2008;Uezu et al, 2016). The functional diversification of synapses is often related to their molecular diversity.…”
Section: Introductionmentioning
confidence: 99%
“…The functional diversification of synapses is often related to their molecular diversity. It has been reported that many synaptic proteins, including different subtypes of receptors, isoforms of scaffolding proteins and adhesion molecules, are differentially expressed in various brain regions (Bayes et al, 2012(Bayes et al, , 2011Collins et al, 2006;Emes et al, 2008;Frank et al, 2016;Frank, Zhu, Komiyama, & Grant, 2017;Husi, Ward, Choudhary, Blackstock, & Grant, 2000;Komiyama et al, 2002;Lein et al, 2007;Micheva, Busse, Weiler, O'Rourke, & Smith, 2010;Roy et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of mutations implicated in neurodevelopmental disorders specifically led to the “synaptic hypothesis” that neurodevelopmental disorders result from impaired assembly and/or maintenance of synapses (Gigek et al., ). Elongation factors have certainly been shown to be key in the lasting potentiation of synapses (Giustetto et al., ; Roy et al., ). Both isoforms of eEF1A have been reported to be present at synapses and to have a role in clustering of gephyrin, a scaffold protein involved in anchoring receptor molecules to postsynaptic membranes (Becker, Kuhse, & Kirsch, ).…”
Section: Why Do Mutations In Genes With Housekeeping Functions Lead Tmentioning
confidence: 99%